COMPENSATION, WORK ENVIRONMENT, AND MOTIVATION AS PREDICTORS OF EMPLOYEE JOB SATISFACTION - Akbar Agapitus; Nina Fitriana; Herlan Djunaidi; Irayani; Yolanda Veybitha (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of compensation, work environment, and work motivation on employee job satisfaction at Kursus Kampung Inggris Tempirai, PALI Regency. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 43 respondents. The data analysis technique used is multiple linear regression with SPSS version 26. The results show that compensation, work environment, and work motivation have a positive and significant effect on employee job satisfaction, both partially and simultaneously. The F-test result shows a significance value of 0.000 (< 0.05), indicating that all independent variables simultaneously affect job satisfaction. The t-test results also indicate that each independent variable has a significant individual effect on job satisfaction. Therefore, improving compensation systems, creating a supportive work environment, and increasing employee motivation are essential strategies to enhance job satisfaction